2020
DOI: 10.3832/ifor3371-013
|View full text |Cite
|
Sign up to set email alerts
|

The natural recovery of disturbed soil, plant cover and trees after clear-cutting in the boreal forests, Russia

Abstract: Biogeosciences and Forestry Biogeosciences and Forestry The natural recovery of disturbed soil, plant cover and trees after clear-cutting in the boreal forests, Russia Aleksey Ilintsev (1-2) , Alexander Bogdanov (1-2) , Elena Nakvasina (2) , Irina Amosova (3) , Sergey Koptev (2) , Sergey Tretyakov (2) This study aims to determine the impact of forest harvesting machinery on the temporarily moist soil of spruce forests (Picea abies Karst.) during the summer. For research purposes, we investigated 23 sites of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
2
8
0
1
Order By: Relevance
“…The study of the regeneration distribution over the EC and its determinant factors confirmed our previous findings [31] of the four distinct zones: forest, a transition from forest to clear-cut under forest canopy, a transition from forest to clear-cut beyond forest scant in the surveyed stands, it does populate clear-cuts very actively, propagating by root sprouts and seeds [56]. Prickly rose, like rowan, is a widespread understory species but is more light-demanding [57] and forms single-species stands in open sites.…”
Section: Environment Characteristics In the Forest Transitional Zone And The Clear-cutsupporting
confidence: 84%
See 1 more Smart Citation
“…The study of the regeneration distribution over the EC and its determinant factors confirmed our previous findings [31] of the four distinct zones: forest, a transition from forest to clear-cut under forest canopy, a transition from forest to clear-cut beyond forest scant in the surveyed stands, it does populate clear-cuts very actively, propagating by root sprouts and seeds [56]. Prickly rose, like rowan, is a widespread understory species but is more light-demanding [57] and forms single-species stands in open sites.…”
Section: Environment Characteristics In the Forest Transitional Zone And The Clear-cutsupporting
confidence: 84%
“…Birch is known for frequent and abundant seed-bearing and intensive growth [58,59]. It can, therefore, rapidly capture the released spaces, occupying the dominant position [56]. Another factor is its capacity for vegetative propagation-after a stand comprising birch is logged down, birch begins to regenerate rapidly and grow actively [60].…”
Section: Time Since Cuttingmentioning
confidence: 99%
“…This suggests that reforested sites could recover during the first 30-year period. Previous studies found that different types of silvicultural management highly modify ground vegetation, even under the same tree species (Tyle 1989;Ilintsev et al 2020;Marozas and Sasnauskienė 2021). For example, shelter wood cuttings in Scots pine stands resulted in an increase of herbaceous species but decreased the abundance of mosses and lichens (Marozas and Sasnauskienė 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It was also noticed that species richness increased after clear-cutting. Changes in microenvironmental conditions create new ecological niches that lead to changes in plant cover and composition and the emergence of different ecological cenotic groups (Ilintsev et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation